Witness to murder - Dixon, Franklin W. (Archway New York, 1988)
Witness to Murder is a suspenseful thriller that centers around the harrowing experience of a woman named Sarah, who inadvertently becomes a witness to a brutal crime. After witnessing a murder from her apartment window, she finds herself drawn into a web of danger as the killer realizes she saw everything. As Sarah grapples with her fear and uncertainty, she must navigate the treacherous landscape of police investigations, media scrutiny, and the looming threat of the murderer seeking to silence her. The story explores themes of courage, survival, and the moral dilemmas faced when confronting evil, culminating in a tense race against time to seek justice and protect her life.